2009
DOI: 10.1002/macp.200900254
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Aluminum Colored Pigments Based on Gradient Copolymers Design

Abstract: A colored polymer/aluminium hybrid pigment was synthesized by nitroxide mediated polymerization initiated from an inorganic surface. This approach requires the preparation of a vinyl dye monomer able to copolymerize with n‐butyl acrylate (n‐BuA) and styrene (S) from the surface of aluminium flakes. The linearity of the ln([M]0/[M]t) and of the $\overline M _{\rm n}$ as a function of time and conversion constitute the criteria of control/“living” polymerization, i.e. linearity of respectively ln([M]0/[M]t) = f(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…It is worth mentioning here that similar dye-functionalized copolymer brushes were also immobilized on aluminium flakes by SI-NMP using a related approach, leading to colored pigments [251].…”
Section: Elaboration Of Mica-based Composites With Tailored Optical P...mentioning
confidence: 99%
“…It is worth mentioning here that similar dye-functionalized copolymer brushes were also immobilized on aluminium flakes by SI-NMP using a related approach, leading to colored pigments [251].…”
Section: Elaboration Of Mica-based Composites With Tailored Optical P...mentioning
confidence: 99%
“…A colored polymer/aluminum hybrid pigment was synthesized by copolymerizing with n -butyl acrylate and styrene on the surface of aluminum pigments. They found that both the length of the grafted chains and the dye/styrene molar ratio influenced the color of the resultant hybrid material [28].…”
Section: Introductionmentioning
confidence: 99%
“…A great number of hybrid organic/inorganic composites have been developed these last year using many procedures based on polymer chemistry . In fact, a multiple technological and fundamental applications were used depending of the size, the nature and the shape of the inorganic particles . On the other hand, they were based on both the physicochemical polymer adsorption or on the surface initiated polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption or coating of neutral polymers onto mineral supports (silica gel, alumine, …) was largely studied . Comparatively, the modification of mica using polyelectrolyte polymers is relatively new.…”
Section: Introductionmentioning
confidence: 99%